A comparison of epidural analgesia provided by Bupivacaine plus Pethidine, Bupivacaine plus Morphine, or Bupivacaine plus Morphine plus Midazolam for lower limb Orthopaedic surgery - Sharma, NR; Rai, U; Panthee, S; Shrestha, P (Journal of Chitwan Medical College, 2014)
Epidural anaesthesia and analgesia in orthopaedic surgeries helps to prevent thromboembolic phenomenon by increasing venodynamics. Adequate post operative analgesia with good patient satisfaction has been observed with this technique. The objective of this study was to assess the duration of postoperative analgesia and complications in patients receiving epidural anesthesia with morphine, midazolam and pethidine in combination with bupivacaine. We prospectively studied 75 Patients who were scheduled for elective lower limb orthopaedic surgery with epidural anaesthesia. This study was conducted from March 2010 to March 2012 at Lumbini Medical College Palpa. They were randomly divided by lottery method into three equal groups. Group ‘A’ (BP) received 50 mg epidural pethidine (3 ml) with 0.5 % bupivacaine 13 ml. Group ‘ B’ (BM) received 5 mg (3 ml) epidural morphine with 13 ml of 0.5% bupivacaine and Group’ C’ (BMM) received 5 mg (1 ml) epidural morphine with 13 ml 0.5% bupivacaine and 2 mg (2 ml) epidural midazolam. All the patients were observed for 24 hours for quality of analgesia and other side effects like nausea vomiting, and pruritus. Data were analysed by SPSS-16.0 software. The result of the study shows the duration of analgesia was prolonged in BMM group than BM, and BP group and was statistically significant (P value <0.001). Incidence of nausea and vomiting in BMM group was lower than that of BP and BM group but was statistically insignificantly (P value 0.489). Pruritus was absent in BP group and was more with BM and BMM group (P value 0.007). In conclusion the use of epidural morphine and midazolam in combination with bupivacaine is the satisfactory method of post operative analgesia. By adding midazolam, duration of analgesia can be increased with decrease in incidence of nausea, vomiting and pruritus. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10842 Journal of Chitwan Medical College 2014; 4(1): 19-21